Village-Campus-Red Cross Collaboration for Voluntary Blood Donation in Cirebon - Nurallia Sumanti; Ardi Liany Purnah Wirawan; Dita Puspita; Siti Sopiyatul Munawaroh (SOCIRCLE : Journal Of Social Community Services, 2023)
This community service program described the implementation and immediate outputs of a one-day collaborative blood donation drive in Kertawinangun Village, Kedawung District, Cirebon, Indonesia. The activity was conducted on 3 February 2024 by the Cirebon Indonesian Red Cross, the village government, and STIE Cirebon. The program comprised logistical preparation, pre-donation information, registration, confidential clinical screening, blood collection by authorized personnel, post-donation observation, and brief participant feedback. Evaluation used descriptive process and output indicators covering participant characteristics, screening eligibility, completed donations, blood bags collected, and immediate responses. Twenty-five people registered, including 8 men and 17 women. Seventeen participants (68%) met the screening requirements and completed donation, producing 17 blood bags; 8 participants (32%) were temporarily deferred. Brief feedback indicated that some participants initially feared the procedure but reported relief and satisfaction after donation. The program demonstrated a feasible village-campus-Red Cross role-sharing model: the village mobilized participants and provided the venue, the campus team supported nonclinical operations, and the Red Cross managed screening and blood collection. Because no standardized pretest, posttest, or longitudinal follow-up was used, the program does not claim changes in knowledge or repeat-donation behavior. Future activities should include structured education evaluation, aggregate deferral records, and follow-up communication for eligible and temporarily deferred donors.